Religious Moderation Scale (RM-S): Validitas, Reliabilitas dan Implikasinya dalam Bimbingan dan Konseling - Monalisa, Monalisa; Syaputra, Yogi Damai; Ummah, Yoyoh Khoirotul; Muhamad, Akmal Fatah (Universitas Islam Negeri Madura, 2023)
An understanding of religious moderation is needed by someone. To measure the level of understanding of one's religious moderation, valid and reliable measurement tools are needed. The instrument for measuring the level of understanding of religious moderation has not been found as the basis for this research. This study aims to produce valid and reliable measurement tools in measuring the level of understanding of students' religious moderation. This study used a quantitative method with a cross sectional design. Validity test is done by analyzing the pearson product moment technique. The reliability test was analyzed using the cronbach alpha technique. The indicators of this research cover four aspects, namely 1) national commitment; 2) tolerance; 3) non-violence; 4) accommodative to local culture. The results of this study are named with the scale of religious moderation (RM-S). This scale produces 24 (twenty four) valid statements with a value of Sig. <0.05. The religious moderation scale has a reliability level of 0.841 with details of 8 items for indicators of national commitment, 6 items for indicators of tolerance, 7 items for indicators of non-violence and 5 items for indicators of accommodating local culture. This scale can be used by counselors and subsequent researchers to measure the level of understanding of students' religious moderation. The findings can be the basis for counselors in determining appropriate guidance and counseling interventions or services to increase students' understanding of religious moderation.